A legislative history of the Philippine Drug Law (Republic Act 9165 of 2002 - Comprehensive Dangerous Drugs Act of 2002) from 2002 to 2014 - Perez, Thurgood John Alvarez (Animo Repository, 2021)
The War on Drugs has been one of the most pressing issues that has defined the current state of our country’s politics today. It is a topic of much controversy due to how the government handles the situation with an iron-fisted viewpoint, and this has often led to the media focusing on aspects such as the high body counts amongst the suspects. Amidst all these, not much has been given to re-examining the standing laws in our country regarding the handling of crimes related to illegal drugs and related substances. This study aims to look into our current drug law, Republic Act No.9165 (Comprehensive Dangerous Drugs Act of 2002). It will essentially be a legislative history of the law, tracing its development in the Senate and Congress to seeing how past experiences with drugs influenced it. The study aims to provide a better understanding into the legal, and social workings of combating illegal drugs and substances, and perhaps provide insight as to whether it is in need of change, given today’s perspectives.